The gods of the sea : whales and coastal communities in northeast Japan, c.1600-2019 - Holm, Fynn (Cambridge University Press, 2023)
Japan is often imagined as a nation with a long history of whaling. In this innovative new study, Fynn Holm argues that for centuries some regions in early modern Japan did not engage in whaling. In fact, they were actively opposed to it, even resorting to violence when whales were killed. Resistance against whaling was widespread especially in the Northeast among the Japanese fishermen who worshiped whales as the incarnation of Ebisu, the god of the sea. Holm argues that human interactions with whales were much more diverse than the basic hunter-prey relationship, as cetaceans played a pivotal role in proto-industrial fisheries. The advent of industrial whaling in the early twentieth century, however, destroyed this centuries-long equilibrium between humans and whales. In its place, communities in Northeast Japan invented a new whaling tradition, which has almost completely eclipsed older forms of human-whale interactions. This title is also available as Open Access.
Title from publisher's bibliographic system (viewed on 14 Aug 2023).
Keywords: Whaling -- Japan -- History.; Whaling -- Social aspects -- Japan -- History.; Japan -- History -- Tokugawa period, 1600-1868.; Japan -- History -- 1868-